Tomato Concentrates Inhibit Platelet Function and Thrombus Formation in Rats - Irfan, Muhammad; Hee Rhee, Man (Pakistan Journal of Nutrition, 2017)
Background and Objective: Ethnomedicine and natural products have revitalized the interest in traditional remedies that are being used in prophylactic regimes for cardiovascular diseases. Consumption of tomato and tomato products reduces the hyper-activation of platelets and the process of atherosclerosis and hence reduces the incidence of cardiovascular diseases. The objective of this study was to investigate the antiplatelet activity of water-soluble tomato concentrate (WSTC) and dry water-soluble tomato concentrate (DWSTC) in a detailed manner to identify the underlying mechanism using ex vivo and in vivo experiments with rat platelets for demonstrating the benefits of the dietary supplementation of tomato concentrates which are equivalent to human doses. Methodology: Aggregation was induced by adenosine diphosphate (ADP) and the extent of aggregation was determined using light transmission aggregometry. Granule-secretion, [Ca2+]i and thromboxane B2 were examined. Phosphorylation of signaling molecules, including mitogen-activated protein kinase (MAPK), was investigated by immunoblotting. Prothrombin time and activated partial thromboplastin time were also examined. Moreover, in vivo thrombus wet weight was tested by arteriovenous bypass thrombosis. Results: Both concentrates significantly inhibited agonist-induced platelet aggregation, serotonin release, [Ca2+]i and thromboxane B2 concentration induced by ADP. Moreover, phosphorylation of MAPK pathway factors, i.e., ERK, JNK and P38, was reduced. The concentrates inhibited in vivo thrombus formation without affecting prothrombin time and activated partial thromboplastin time. Conclusion: Both concentrates possess ethnomedicinal properties to prevent cardiovascular ailments and can be used as a functional food or dietary supplement.